2016
DOI: 10.1093/jac/dkw529
|View full text |Cite
|
Sign up to set email alerts
|

Finafloxacin overcomesBurkholderia pseudomalleiefflux-mediated fluoroquinolone resistance

Abstract: human-to-animal transfer through close contacts. In our study, the OXA-48-positive animal was living in France, where OXA-48 is not endemic in humans. 6 This suggests that OXA-48 producers in animals might be underreported in OXA-48-endemic countries. The origin of the OXA-48 E. coli in this dog could not be traced. No bla CTX-M-15 gene was identified along with bla OXA-48 , a combination that is, on the contrary, rather common in human isolates. Also, carbapenem-susceptible ST372 E. coli isolates have alread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The probability of any one gene being mutated seven times given our dataset is 1.65x10 -23 . Homologs of this locus in other Burkholderia species are annotated as bpeT , which is strongly associated with drug resistance [3436]. A locus with five multiple mutations (P = 6.48x10 -16 ) encodes N-acetylmuramoyl-L-alanine amidase (AmpD, BMUL_2790), which is associated with resistance to β-lactam antibiotics [30].…”
Section: Resultsmentioning
confidence: 99%
“…The probability of any one gene being mutated seven times given our dataset is 1.65x10 -23 . Homologs of this locus in other Burkholderia species are annotated as bpeT , which is strongly associated with drug resistance [3436]. A locus with five multiple mutations (P = 6.48x10 -16 ) encodes N-acetylmuramoyl-L-alanine amidase (AmpD, BMUL_2790), which is associated with resistance to β-lactam antibiotics [30].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that the oral formulation of finafloxacin has utility in treating infection with the biothreat agent Burkholderia pseudomallei in a BALB/c mouse model of melioidosis (Barnes et al, 2017). It has been suggested that this superior efficacy at infection-relevant pH (in addition to its activity at neutral pH) is due to ability to maintain activity and not be affected by efflux (Randall et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Doxycycline and ciprofloxacin were used as control antibiotics, as they are prone to efflux, particularly by the BpeEF-OprC pump in B. pseudomallei (41, 48). The observed MIC for GC-072 against B.…”
Section: Resultsmentioning
confidence: 99%
“…Bp320 is a Δ( bpeEF-oprC ) derivative of Δ( amrAB-oprA ) Δ( bpeAB-oprB ) strain Bp282 and was constructed using the previously described methods. This strain does not express any known efflux pumps (48). bThe MIC against each strain was determined using broth microdilution assays.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation